Cambridge companion to modern Russian culture - Rzhevsky, Nicholas (Cambridge companions to culture, 2012)
"Russia's size, the diversity of its peoples and its unique geographical position straddling East and West have created a culture that is both inward and outward looking. Its history reflects the tension between very different approaches to what culture can and should be, and this tension shapes the vibrancy of its arts today. The highly successful first edition of Rzhevsky's Companion has been updated to include post-Soviet trends and new developments in the twenty-first century. It brings together leading authorities writing on Russian cultural identity, its Western and Asian connections, popular culture and the unique Russian contributions to the arts. Each of the eleven chapters has been revised or entirely rewritten to take account of current cultural conditions and the further reading brought up to date. The book reveals, for students, academic researchers and all those interested in Russia, the dilemmas, strengths and complexities of the Russian cultural experience"--